Implementasi Perdana Program Rotate Your Book: Strategi Inovatif Literasi Di SD Negeri Demangan - Ni Ketut Ayu Nirmala Dewi; Diyan Rizki Perdana (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This study aims to analyze the initial implementation of the Rotate Your Book program at SD Negeri Demangan as a collaborative strategy to enhance student literacy. The program was conducted through a book-exchange activity on November 14, 2025, in collaboration with the Yogyakarta City Library and Archives Office. This research employed a descriptive qualitative approach, using observation, interviews, and document analysis as data collection methods. The findings indicate that the program improves access to reading materials, fosters students’ reading interest, and encourages active participation in literacy activities. However, limitations in the quantity and variety of children's book collections prevented some students from obtaining suitable replacement books. Overall, the program is considered effective as a collaborative public–school literacy innovation model. The study highlights the importance of strengthening collection curation and user-based literacy evaluation systems. Recommendations include mapping students’ reading interests, adjusting collections based on user needs, and involving teachers in the curation process. This program has the potential to be replicated as a literacy development model in public elementary schools.